2003
DOI: 10.1038/ng1099
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 functions as a tumor suppressor in mouse skin

Abstract: Notch proteins are important in binary cell-fate decisions and inhibiting differentiation in many developmental systems, and aberrant Notch signaling is associated with tumorigenesis. The role of Notch signaling in mammalian skin is less well characterized and is mainly based on in vitro studies, which suggest that Notch signaling induces differentiation in mammalian skin. Conventional gene targeting is not applicable to establishing the role of Notch receptors or ligands in the skin because Notch1-/- embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
817
3
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 896 publications
(878 citation statements)
references
References 28 publications
49
817
3
9
Order By: Relevance
“…The consequences of such dysregulation does however seem to be highly cell type specific. For example, the constitutively activated form of Notch acts as a bona fide oncogene in leukaemia and in murine breast cancer, while recent data show that Notch-1 can function as a tumour suppressor gene in skin cancer (Ellisen et al, 1991;Uyttendaele et al, 1996;Nicolas et al, 2003). It has been suggested that these disparate effects might be dependent of the normal function of the cascade, that is, in tissues were Notch signalling is active in progenitor cells followed by a decreased signalling in differentiated cells, a constitutive activation of the cascade might lead to blocked differentiation or increased survival and proliferation (Allenspach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of such dysregulation does however seem to be highly cell type specific. For example, the constitutively activated form of Notch acts as a bona fide oncogene in leukaemia and in murine breast cancer, while recent data show that Notch-1 can function as a tumour suppressor gene in skin cancer (Ellisen et al, 1991;Uyttendaele et al, 1996;Nicolas et al, 2003). It has been suggested that these disparate effects might be dependent of the normal function of the cascade, that is, in tissues were Notch signalling is active in progenitor cells followed by a decreased signalling in differentiated cells, a constitutive activation of the cascade might lead to blocked differentiation or increased survival and proliferation (Allenspach et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the keratinocyte‐specific ablation of NOTCH1 induced significant proliferation of the basal epidermal layer and deregulated expressions of multiple differentiation markers, indicating disrupted balance between growth and differentiation 29. In a later research using similar conditional gene deletion technology, effects of long‐term NOTCH1 deficiency were further characterized 30. The induced Notch1 ‐/‐ adult mice showed epidermal hyperplasia followed by formation of skin tumors.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%
“…In the epidermis of induced Notch1 ‐/‐ mice, significantly high levels of free (unphosphorylated) beta‐catenin were observed 30. Loss of Notch1 signaling seems to activate beta‐catenin signaling in human CSCC 28, which can be repressed by the introduction of a dominant active form of NOTCH130.…”
Section: Notch Signaling In Cutaneous Squamous Cell Carcinoma (Cscc)mentioning
confidence: 99%
See 2 more Smart Citations